Impact assessment of improved wheat variety disseminated through farmer participatory research in Palwal district of Haryana - Burman, R Roy; Sharma, J P; Sharma, Shailendra; Singh, Rahul; Rao, D U M; Singh, A K (The Indian Journal of Agricultural Sciences, 2020)
In a study involving large-scale farmer participatory field trials for evaluating the performance of a recently released improved wheat variety, HD 3086 (Pusa Gautami) in 300 farmers’ fields in three villages of Palwal district, significantly yielded higher grain and straw output compared to output of control group with the same existing resources. Adoption curves were generated to ascertain the rate of adoption and diffusion of HD 3086 among farmers of FFP villages and neighbouring villages. The rate of adoption of HD 3086 was more than 16 times on acreage basis in the span of three years.